Идеология и экспертное знание - Голованов, Борис Дмитриевич (My University, 2015)
Статья посвящена трансформациям социального знания в постсоветском обществе. Автор производит сопоставление когнитивных статусов идеологии и экспертного знания в современном политическом сознании и практике. Анализируются методологические и ценностные предпосылки, лежащие в основании экспертного знания.

The article deals with the transformation of social knowledge in post-Soviet society. The author makes a comparison of the ideology cognitive statuses and expert knowledge in modern political consciousness and practice. It analyzes the methodological background and the values that lie at the base of expert knowledge.
Ideology and expert knowledge
Keywords: экспертное сообщество; политические субъекты; конституирование; инструментализация науки; expert community; expert community; political subjects; instrumentalization of science